1989
DOI: 10.1111/j.1526-4610.1989.hed22904233.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Prostaglandins in True Menstrual Migraine

Abstract: Eighteen patients suffering from true menstrual migraine and 12 control subjects were studied. We evaluated in different phases of the menstrual cycle and during the migraine crisis the peripheral plasma concentrations of 6-keto-PGF1 alpha (the stable metabolite of PGI2), thromboxane B2 (the stable metabolite of thromboxane A2), PGF2 alpha and PGE2. The mean values of 6-keto-PGF1 alpha in menstrual migraine sufferers are lower than in normal women throughout the whole cycle. The difference between the trends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 36 publications
2
40
1
5
Order By: Relevance
“…Different types of prostaglandin play a role in the pathogenesis of migraine [7, 8], and increased levels of plasma prostaglandin E 2 have been found during the pain phase in women with menstrual migraine [9]. Interestingly, it has been shown that endometriosis is associated with a significant increase in prostaglandin production [10,11,12]; therefore, it is possible to hypothesize that the systemic spreading of prostaglandins produced by endometriosis lesions may contribute to the increased prevalence of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of prostaglandin play a role in the pathogenesis of migraine [7, 8], and increased levels of plasma prostaglandin E 2 have been found during the pain phase in women with menstrual migraine [9]. Interestingly, it has been shown that endometriosis is associated with a significant increase in prostaglandin production [10,11,12]; therefore, it is possible to hypothesize that the systemic spreading of prostaglandins produced by endometriosis lesions may contribute to the increased prevalence of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…First, prostaglandins sensitize peripheral nociceptors to pain and are potent mediators of hyperalgesia [9]. Second, prostaglandins such as prostaglandin F 2 increase during an acute migraine attack [10]. Third, injections of prostaglandin E 2 can produce migraine-like headaches in non-migraineurs [11].…”
Section: Prostaglandin Release Theorymentioning
confidence: 99%
“…This cyclical drop in hormone concentrations might trigger an abnormal biohumoral reaction [9][10][11][12][13], partially explaining the different clinical features and perhaps also the different responses to abortive and prophylactic therapy that usually, but not always, occur between menstrual and nonmenstrual attacks [14,15]. MM attacks are generally long and may last even more than the 72 h upper limit proposed for migraine without aura in the IHS classification [3].…”
Section: Clinical Aspectsmentioning
confidence: 99%